Erratum. Issue 10 (1st October 2016) - Unknown
Abstract : This erratum corrects an error in the article, "Comparing Low‐Flow Accuracy of Mechanical and Electronic Meters, " by McKenna L. Sumrak, Michael C. Johnson, and Steven L. Barfuss, in the June 2016 issue of Journal AWWA (Vol. 108 No. 6, p. E327). The error was found inTable 3 for the value for the nutating disc meter type in the 1–8 column.